Tatalaksana Penurunan Kesadaran Pada Penderita Diabetes Mellitus - Ian Huang (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Hyperglycemic crisis (diabetic ketoacidosis or hyperosmolar hyperglycemic state), lactic acidosis, hypoglycemia, and uremic encephalopathy are life-threatening complications of diabetes mellitus (DM). Specific therapies of each condition are essential in reducing mortality rate of the complications.